2013
DOI: 10.1016/j.jval.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Baseline Low-Dose Computed Tomography Screening for Lung Cancer: The Israeli Experience

Abstract: Our analysis suggests that baseline LDCT lung cancer screening in Israel presents a good value for the money and should be considered for inclusion in the National List of Health Services financed publicly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Although some modellers have presumed that lung cancer develops sufficiently rapidly to produce lead times of around 2 years, [126][127][128] those actually engaged in screening have been more circumspect. Development times of 6 and 8 years between stages 1 (if screen detected) and four (if presenting) have been suggested for Japan 129 and ELCAP, 130 respectively, and these figures set the upper limits on lead times.…”
Section: Lead Timementioning
confidence: 99%
See 1 more Smart Citation
“…Although some modellers have presumed that lung cancer develops sufficiently rapidly to produce lead times of around 2 years, [126][127][128] those actually engaged in screening have been more circumspect. Development times of 6 and 8 years between stages 1 (if screen detected) and four (if presenting) have been suggested for Japan 129 and ELCAP, 130 respectively, and these figures set the upper limits on lead times.…”
Section: Lead Timementioning
confidence: 99%
“…The model was re-estimated for annual screening and yielded baseline estimates of £19,060 or £31,800, depending on whether the model's cancer stage predictions derived from the ELCAP-or the NLST-reported stage shift. 141 Finally, a study in Israel 128 reported QALY gains of around 0.06 per person screened, along with an ICER of only £1005 per QALY gained.…”
Section: Comparison With Other Estimatesmentioning
confidence: 99%
“…Az irodalomkutatás során 16 olyan költség-hatékonysági modellt találtunk a szakirodalomban, amely az alacsony dózisú CT-vel történő tüdőrákszűrést értékeli (1. táblá-zat) [8,11,[22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Black és mtsai az NLST vizsgálat mentén készült értékelésükben az alacsony dózisú CTvel történő szűrést a szűrés elmaradásának alternatívájá-val, valamint a mellkasröntgennel való szűréssel is össze-vetették.…”
Section: Költség-hatékonysági Modellekunclassified
“…The consensus of favorable cost-benefit across recent studies is remarkable, because the studies have varied in many ways, including the national system modeled and the populations modeled (2)(3)(4)(5), the bases of costs and mortality, the projection period, whether inflation or discounting were considered and other methodological issues. Lung cancer screening is truly robust.…”
mentioning
confidence: 99%